High-Minority Nursing Homes Disproportionately Affected by COVID-19 Deaths - Weech-Maldonado, Robert; Lord, Justin; Davlyatov, Ganisher; Ghiasi, Akbar; Orewa, Gregory (Frontiers in Public Health, 2021)
Racial/ethnic disparities in healthcare have been highlighted by the recent COVID-19 pandemic. Using the Centers for Medicare and Medicaid Services' Nursing Home COVID-19 Public File, this study examined the relationship between nursing home racial/ethnic mix and COVID-19 resident mortality. As of October 25, 2020, high minority nursing homes reported 6.5 COVID-19 deaths as compared to 2.6 deaths for nursing homes that had no racial/ethnic minorities. After controlling for interstate differences, facility-level resident characteristics, resource availability, and organizational characteristics, high-minority nursing homes had 61% more COVID-19 deaths [Incidence Rate Ratio (IRR) = 1.61; p < 0.001] as compared to nursing facilities with no minorities. From a policy perspective, nursing homes, that serve primarily minority populations, may need additional resources, such as, funding for staffing and personal protective equipment in the face of the pandemic. The COVID-19 pandemic has sharpened the focus on healthcare disparities and societal inequalities in the delivery of long-term care.